Norway Spruce Balm: Phytochemical Composition and Ability to Enhance Re-epithelialization In Vitro - Goels, Thomas; Eichenauer, Elisabeth; Langeder, Julia; Hoeller, Franziska; Sykora, Christina; Tahir, Ammar; Urban, Ernst; Heiss, Elke H.; Saukel, Johannes; Glasl, Sabine (Planta Medica, 2020)
The balm of the Norway spruce (Picea abies) is a well-known traditional herbal medicine used to cure wounds. Even though clinical trials have confirmed its empirical use, the active constituents, their mode of action, and the exact composition of this natural product are still unknown. In this study, the balm was subjected to fractionated extraction and further purified employing flash chromatography, HPLC-PDA-ELSD, preparative and analytical TLC. Hydroxycinnamic acids (1–3), the lignan pinoresinol (4), four hydroxylated derivatives of dehydroabietic acid (DHAA) (5 – 8), and dehydroabietic acid (9) were isolated. Their structures were elucidated by LC-MS, 1D- and 2D-NMR. Four extracts, two commercially available resin acids–pimaric acid (10) and isopimaric acid (11)–and the isolated compounds were tested for increased re-epithelialization of cell-free areas in a human adult low calcium high temperature keratinocytes monolayer. Lysophosphatidic acid (10 µM) served as positive control and ranged between 100% and 150% rise in cell-covered area related to the vehicle control. Two extracts containing carboxylic acids and non-acidic apolar constituents, respectively, boosted wound closure by 47% and 36% at 10 and 3 µg/mL, respectively. Pinoresinol, DHAA, three of its hydroxylated derivatives, and pimaric and isopimaric acid as well as defined combinations of the hydroxylated DHAA derivatives led to a significantly enhanced wound closure by up to 90% at concentrations between 1 and 10 µM. Overall, lignans and diterpene resin acids, main constituents of Norway spruce balm, are able to increase migration or proliferation of keratinocytes in vitro. The presented data link the phytochemistry of this natural wound healing agent with boosted re-epithelialization.
Keywords: Picea abies; Pinaceae; wound healing; balm; resin; keratinocytes